看中文电影的次数与汉语听力能力的关系—— 以KRISTEN HOSANA 高中一学生为例 HUBUNGAN INTENSITAS MENONTON FILM DALAM BAHASA MANDARIN DENGAN KEMAMPUAN MENYIMAK BAHASA MANDARIN SISWA KELAS X SEKOLAH KRISTEN HOSANA MEDAN - Ng Sugiroto Sugiroto; Evelyn Homan (Journal of Language, Literature and Teaching, 2022)
The purpose of this research was to find out whether the number/amount of chinese movies watched by 1st grade of Kristen Hosana high school students would have positive impact with their mandarin listening ability. This research/study used quantitive research/study method, with 42 1st grade high school students of Kristen Hosana as the subjects. The test used in this paper are from YCT 3rd level questions, therefore the validity and reliability are trustworthy. Afterward used Excel software to process the data into data description display. Through the result of the data calculation of correlation analysis it can be known that r = 0.69 and refering to the interpretation of the correlation coefficient, the relationship between these two variables is high. These two variables were significantly related (t = 6). Therefore it can be concluded that the number of chinese movies watched by 1st grade high school students of Kristen Hosana is significantly related(affected) their listening ability.